2022
DOI: 10.3389/fcimb.2022.896978
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Minimum Biofilm Eradication Concentration (MBEC) on In Vivo Biofilm on Orthopedic Implants in a Rodent Femoral Infection Model

Abstract: The formation of a biofilm on the implant surface is a major cause of intractable implant-associated infection. To investigate the antibiotic concentration needed to eradicate the bacteria inside a biofilm, the minimum biofilm eradication concentration (MBEC) has been used, mostly against in vitro biofilms on plastic surfaces. To produce a more clinically relevant environment, an MBEC assay against biofilms on stainless-steel implants formed in a rat femoral infection model was developed. The rats were implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…VAN also showed a similar trend when tested using a methicillin-resistant S. aureus strain. 54 Taking these findings into consideration, we believe that the preliminary data obtained using a 48-hour-old biofilm provide useful insights about the biofilm destructive action of RIF combinations eluted via CaS/HA carrier. Finally, an analysis of the mechanical properties of CaS/HA alone and in combination with antibiotics was lacking in this study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…VAN also showed a similar trend when tested using a methicillin-resistant S. aureus strain. 54 Taking these findings into consideration, we believe that the preliminary data obtained using a 48-hour-old biofilm provide useful insights about the biofilm destructive action of RIF combinations eluted via CaS/HA carrier. Finally, an analysis of the mechanical properties of CaS/HA alone and in combination with antibiotics was lacking in this study.…”
Section: Discussionmentioning
confidence: 88%
“… 29 , 44 For biofilm eradication we used a 48-hour-old immature biofilm rather than a 14-day-old biofilm, which is the reported time for biofilm maturation post-infection. 53 However, in a recent study Okae et al 54 reported that the MBEC of GEN and cefazolin obtained on 72-hour-old biofilms was similar to or even twice that of 14-day-old biofilms. VAN also showed a similar trend when tested using a methicillin-resistant S. aureus strain.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of S. aureus biofilm using Calgary biofilm device [ 58 ], the clinical isolate in biofilm tolerated up to 4 × MIC ampicillin. In other studies of S. aureus biofilm in 96-well plate [ 64 ] and on an orthopedic implant surface [ 65 ], it was shown an increased tolerance up to 8000 × MIC and 256 × MIC vancomycin, respectively, after 24 h of treatment (Calculations were based on division of the study-determined MBEC and MIC).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49] Both in vitro and in vivo generated biofilms show cefazolin tolerance over 250× MIC. 20 Notably, cefazolin and other antibiotics appear to be more effective at targeting biofilm in combination with rifampicin. 21,50 The main limitation of this model was that it still generated significant soft tissue infection and painful inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…7,17,18 Unfortunately, cefazolin does not kill staphylococcal biofilms on surgical materials at concentrations over 100× its minimum inhibitory concentration (MIC), and S. aureus grown in synovial fluid shows enhanced cefazolin tolerance. 6,19,20 Several rodent studies have demonstrated that systemic cephalosporin treatment fails to eradicate S. aureus bioburden from infected bones or joints. [21][22][23] Overall, the evidence suggests it is not feasible to achieve effective cefazolin concentrations to clear biofilm from the joint, even with maximal systemic clinical dosages.…”
Section: Introductionmentioning
confidence: 99%